Microbes at Surface-Air Interfaces: The Metabolic Harnessing of Relative Humidity, Surface Hygroscopicity, and Oligotrophy for Resilience - Stone, Wendy; Kroukamp, Otini; Korber, Darren R.; McKelvie, Jennifer; Wolfaardt, Gideon M. (Frontiers in Microbiology, 2016)
The human environment is predominantly not aqueous, and microbes are ubiquitous at the surface-air interfaces with which we interact. Yet microbial studies at surface-air interfaces are largely survival-oriented, whilst microbial metabolism has overwhelmingly been investigated from the perspective of liquid saturation. This study explored microbial survival and metabolism under desiccation, particularly the influence of relative humidity, surface hygroscopicity, and nutrient availability on the interchange between these two types of behavior. The combination of a hygroscopic matrix (i.e., clay or 4,000 MW polyethylene glycol) and high relative humidity (RH) resulted in persistent measurable microbial metabolism during desiccation. In contrast, no microbial metabolism was detected at (a) hygroscopic interfaces at low RH, and (b) less hygroscopic interfaces (ie., sand and plastic/glass) at high or low RH. Cell survival was conversely inhibited at high RH and promoted at low RH, irrespective of surface hygroscopicity. Based on this demonstration of metabolic persistence and survival inhibition at high relative humidity, it was proposed that biofilm metabolic rates might inversely influence whole-biofilm resilience, with ‘resilience’ defined in this study as a biofilm’s capacity to recover from desiccation. The concept of whole-biofilm resilience being promoted by oligotrophy was supported in desiccation-tolerant Arthrobacter spp. biofilms, but not in desiccation-sensitive Pseudomonas aeruginosa biofilms. The ability of microbes to interact with surfaces to harness water vapor during desiccation was demonstrated, and potentially to harness oligotrophy (the most ubiquitous natural condition facing microbes) for adaptation to desiccation.